HUBUNGAN NILAI P300 DENGAN MOCAINA PADA PASIEN DENGAN GANGGUAN KOGNITIF VASKULAR PASCASTROKE ISKEMIK - Susilo,* Yudy Goysal,** Abdul Muis,** Muhammad Akbar,** Andi Kurnia Bintang,** Burhanuddin Bahar,*** (Neurona Majalah Kedokteran Neuro Sains, 2019)
INTRODUCTION STROKE IS A MAJOR THREAT IN HUMAN LIFE BECAUSE IT CAN CAUSE DISABILITY AND MORTALITY COGNITIVE IMPAIRMENT IN EARLY STROKE IS STRONG PREDICTOR FOR LONG TERM VASCULAR COGNITIVE IMPAIRMENT WHILE NEUROPSYCHOLOGY METHOD IS SUPERIOR THAN CONVENTIONAL METHOD TO DIAGNOSE COGNITIVE IMPAIRMENT ESPECIALLY P300